2015
DOI: 10.1159/000441225
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Rectal Distension Seen on Prostate Radiotherapy Planning CT Scan Is Not a Negative Prognostic Factor in the Modern Era of Image-Guided Radiotherapy

Abstract: Background: Studies have shown that rectal distension has a significant impact on treatment failure in patients receiving radical radiotherapy for prostate cancer. A distended rectum contributes to excessive organ movement during treatment, resulting in significant underdosing of the target volume and higher treatment failure rates. The increasing use of highly conformal, precise radiotherapy techniques places greater importance on reducing this risk. We tested whether imaging during radiotherapy helps minimis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This study demonstrated a reduced 5-year FFBF in patients with a larger rectal distention on the planning CT-scan compared to those with limited rectal distention (75% vs 89%). Other authors claim that the adverse effects of rectal distention on local control can be compensated by the use of modern IGRT [12] , [28] . Park et al measured CSA on the planning CT-scans in 962 PC patients receiving adaptive RT with a median prescribed dose of 75.6 Gy [28] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study demonstrated a reduced 5-year FFBF in patients with a larger rectal distention on the planning CT-scan compared to those with limited rectal distention (75% vs 89%). Other authors claim that the adverse effects of rectal distention on local control can be compensated by the use of modern IGRT [12] , [28] . Park et al measured CSA on the planning CT-scans in 962 PC patients receiving adaptive RT with a median prescribed dose of 75.6 Gy [28] .…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that initial rectal distention was not significantly associated with reduced 5-years biochemical cancer control or grade ≥ 2 genitourinary and gastrointestinal toxicity, and concluded that adaptive IGRT reduces the risk of geographical miss. Silverman et al examined 172 PC patients receiving conformal RT to a total dose of 74 Gy at a median of 72 months follow up [12] . The rectal diameter was measured at the midpoint of the PTV on the planning CT-scan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rectal distension has been associated with increased biochemical and local progression 34 . However, an awareness of rectal distension in the modern era of RT has enabled clinicians to address this effect 35 . In conclusion, it is recommended that particular care is taken when defining margins at the prostate posterior, acknowledging the trade-off between quality of life due to rectal dose and the preferences of clinicians and patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that interfractional displacement of the prostate gland can vary from 0 to 20 mm due to the changes in the rectum and bladder filling [1][2][3][4][5][6][7][8]. Changes in rectal volume can increase the risk of biochemical and local failure [1,[9][10][11][12][13][14]. An increase in rectal volume receiving ≥ 60 Gy can elevate the https://doi.org/10.3857/roj.2023.00444 AI-driven organ monitoring by MVCT image risk of grade ≥ 2 rectal toxicity, including rectal bleeding, pain or discomfort during bowel movements, diarrhea, and incontinence [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%